Effect of ultrafine fly ash on the properties of concretes containing construction and demolition wastes as coarse aggregates - Shaikh, Faiz (John Wiley and Sons Ltd., 2016)
This paper presents the preliminary results of the effect of ultrafine fly ash (UFFA) on the properties of concretes containing recycled coarse aggregates (RCA) originating from construction and demolition (C&D) wastes. The effect of 10 % UFFA on the compressive strength, tensile strength, sorptivity and chloride ion permeability of concretes containing 25 and 50 % RCA is evaluated at 7, 28 and 56 days. The addition of UFFA increased the compressive strength of recycled aggregate concretes at all ages up to 56 days. However, a slight reduction in the tensile strength of recycled aggregate concretes was observed. Concrete containing 25 % RCA and 10 % UFFA achieved 94 % of the control concrete's compressive strength at 56 days. In both recycled aggregate concretes tested, the sorptivity and chloride ion permeability are much lower at all ages due to the addition of 10 % UFFA. This is because it serves to promote hydration and block the large capillary pores within the concrete.